Ways to conduct lessons for children with speech disabilities with innovative technologies (Eurasian Journal of Learning and Academic Teaching, 2022)
Speech problems in children are one of the most widely studied topics in science. Performing speech exercises from a child’s early age can prevent him or her from developing speech-related defects in the future. In this article, the author describes in detail the work on speech defects in children, the use of innovative technologies in their treatment